Introducing Reliability in Content-Based Publish-Subscribe through Epidemic Algorithms - Costa, Paolo; Migliavacca, Matteo; Picco, Gian Pietro; Cugola, Gianpaolo (The 2nd International Workshop on Distributed Event-Based Systems (DEBS'03), co-located with ACM SIGMOD/PODS, San Diego (CA, USA), 2003)
Distributed content-based publish-subscribe middleware provides the necessary decoupling, exibility, expressiveness, and scalability required by modern distributed applications. Unfortunately, this middleware usually does not provide reliability, especially in the presence of highly recon gurable scenarios. Indeed, this problem has been thus far largely disregarded by the research community and solutions developed in other contexts are not immediately applicable. In this paper, we tackle the problem of introducing reliability in content-based publish-subscribe in dynamic environments by exploiting epidemic algorithms, whose characteristics in terms of decentralization, scalability, and resilience to topological changes resonate with our problem.